2020
DOI: 10.2169/internalmedicine.4375-19
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem Cell Transplantation for Post-essential Thrombocythemia and Post-polycythemia Vera Myelofibrosis

Abstract: Objective Little information is available about the outcome of allogeneic hematopoietic stem cell transplantation (HSCT) for patients with secondary myelofibrosis from essential thrombocythemia (ET) and polycythemia vera (PV). A nationwide retrospective study of the outcome of HSCT for post-ET and post-PV myelofibrosis was conducted in Japan. Patients and Methods Clinical data for patients with post-ET (n=29) and post-PV (n=9) myelofibrosis who had received first alloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previously, Murata et al reported the outcomes of HCT for primary and secondary MF using the nationwide registry database of JSTCT. 36,37 Compared to these studies, more recent patients were included in the current study. A greater number of patients underwent HCT from HLA-mismatched donors, but the clinical outcomes in the studies seemed to be comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Murata et al reported the outcomes of HCT for primary and secondary MF using the nationwide registry database of JSTCT. 36,37 Compared to these studies, more recent patients were included in the current study. A greater number of patients underwent HCT from HLA-mismatched donors, but the clinical outcomes in the studies seemed to be comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Murata et al. reported the outcomes of HCT for primary and secondary MF using the nationwide registry database of JSTCT 36,37 . Compared to these studies, more recent patients were included in the current study.…”
Section: Discussionmentioning
confidence: 99%